Ruthenium brachytherapy for intraocular growth of a conjunctival squamous cell carcinoma: a case report - Rospond-Kubiak, Iwona; Adamski, Wojciech; Sosnowska, Kinga; Kocięcki, Jarosław; Marszałek, Andrzej (Journal of Contemporary Brachytherapy, 2018)
The aim of this study is to report the use of ruthenium brachytherapy as an adjunctive treatment in the management of an intraocular extension of the conjunctival squamous cell carcinoma (SCC). In 2013, a 73-year-old man presented with a tumor blocking the angle and infiltrating corneal endothelium. The patient was treated with iridectomy, and after one month, ruthenium brachytherapy was applied. 4.5 years post-irradiation, the treated eye is painless, and no recurrence was noted. We advocate the use of ruthenium brachytherapy as an eye salvage treatment with an intraocular extension of conjunctival SCC.